ANALISIS KESESUAIAN LAHAN UNTUK PENGEMBANGAN RUANG TERBUKA HIJAU MENGGUNAKAN METODE PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOSPASIAL DI KOTA TANGERANG TAHUN 2023 - Wijdan Khairul Tsany Harli, - (2023)
Development in Tangerang City continues along with rapid growth and has had an impact through significant changes in land use and the decline of green areas. Sustainable urban growth triggers the transformation of green land into built-up areas, creating challenges for preserving green open spaces that have not yet reached the minimum green open space availability of 30%.. The aim of this research is to determine changes in land cover, determine changes in the availability and need for green open space, and analyzing the level of land suitability for developing green open space in Tangerang City. The method in this research uses supervised classification to determine the land cover class and uses the weighted overlay method to determine the level of suitability of green open space development spatially with several indikators used, namely NDVI value, land cover, NDBI value, distance from the road, slope, height, and distance from water bodies. The results of this research showed that there was a change in the area of each land cover class, especially in 2018 the area of built-up land increased by 25.96 〖km〗^2 to 126.31 〖km〗^2in 2023. The land changes that occurred led to a decreaseof green open space from 2018 by 39% or 68.89 km2 to 23% or 40.96 km2, this is below the minimum requirement for green open space availability of 30% based on law. The results of the weighted overlay analysis showed that the level of land suitability for the development of new green open spaces was 26.03 km2 or around 15% to fulfill the need for green open space in the city of Tangerang.